Pengaruh Green Product, Green Promotion dan Green Price Terhadap Keputusan Pembelian Konsumen McDonald’s Malang (Studi Kasus Pada Konsumen McDonald’s Malang) - Pamungkas, Tri Krisna; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The purpose of this study was to measure and examine the "Effect of Green Product, Green Promotion, and Green Price on Consumer Purchasing Decisions at McDonald's (A Case Study on McDonald's Malang Consumers)." This research employed a quantitative method using a questionnaire with a Likert scale of 1-5. The population of this study comprised all consumers who had purchased from and viewed advertisements of McDonald's Malang. The data collection technique utilized a non-probability sampling method, specifically purposive sampling. The sample size for this study was 96 respondents. Data analysis techniques included research instrument tests, classical assumption tests, multiple regression analysis, determination coefficient tests, and t-tests. Data collected were analyzed using IBM SPSS Statistics software. The results of this study indicate that green product has a positive and significant effect on purchasing decisions, green promotion has a positive and significant effect on purchasing decisions, and green price has a positive and significant effect on purchasing decisions at McDonald's Malang outlets. Keywords : Green Product, Green Promotion, Green Price, and Purchase Decision.